1995
DOI: 10.1111/j.1365-2591.1995.tb00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Sealability of the Trifecta™ technique in the presence or absence of a smear layer

Abstract: The aim of this in vitro study was to assess the sealability of a recently introduced thermoplasticized gutta-percha technique (Trifecta, Hygenic Corp., OH, USA) in the presence or absence of a smear layer. A total of 100 teeth with single straight root canals were included in the study. The teeth were decoronated and the canals prepared with a modified double-flared technique under constant irrigation with 2.5% sodium hypochlorite solution. The apical matrix was prepared to size 40 and apical patency subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…It is important to report that smear layer removal by EDTA promotes an increase in dentinal permeability, which has a positive influence on microbial leakage. These results are in agreement with previous investigations which found that removal of smear layer did not enhance the sealing ability (26,27). On the other hand, some studies indicated that the smear layer can act as a barrier to microbial metabolities, preventing microbial invasion into dentinal tubules (28).…”
Section: Discussionsupporting
confidence: 83%
“…It is important to report that smear layer removal by EDTA promotes an increase in dentinal permeability, which has a positive influence on microbial leakage. These results are in agreement with previous investigations which found that removal of smear layer did not enhance the sealing ability (26,27). On the other hand, some studies indicated that the smear layer can act as a barrier to microbial metabolities, preventing microbial invasion into dentinal tubules (28).…”
Section: Discussionsupporting
confidence: 83%
“…Numerous studies have attempted to assess in vitro leakage (4,11,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, there is a great deal of variability in the results and minimal consensus as to the most appropriate method to assess leakage (13,24,25).…”
Section: Discussionmentioning
confidence: 96%
“…Among 44 comparisons, the results of two papers with 4 comparisons, Lloyd et al (30) and Goya et al (33) were not included in the meta-analysis process, because they did not report a valid mean and standard deviation. In addition, one of the comparisons of the Evans and Simon (13) article reported a zero mean and SD, which was automatically excluded from the calculations.…”
Section: Dye Leakage Test Studiesmentioning
confidence: 99%